Vaccines for Tourism Business Actors: Fulfilment or Violation of Human Rights? - I Wayan Gde Wiryawan (PADJADJARAN Jurnal Ilmu Hukum (Journal of Law), 2021)
Tourism sector is the largest source of income for Bali province of Indonesia. Unfortunately, the Covid-19 pandemic forced the closure of tourism. Therefore, Bali’s economic growth is experiencing decrease to -10.98%. To accelerate the reopening of tourism, the government has launched the national vaccine movement that also covers tourism business actors. Unfortunately, some parties resist the vaccination because the vaccine is not believed yet to be safe. By using doctrinal legal research, this study examined two problems: the right to health in the context of tourism and the construction of government policies against vaccine resistance by tourism business actors. It examined legal principles and synchronization of laws on human rights related to vaccination. The state is responsible to provide vaccination for the citizens in fulfilling the right to life and health. Each local government produces policy to deal with vaccine refusal. Jakarta and West Java are two provinces that impose fines for residents who refuse vaccines. On the other hand, Bali province does not impose sanctions on such residents. To ensure safety after the reopening of tourism, any local government can propose the record of vaccination as a requirement for every person who will return to work in the tourism sector.DOI: https://doi.org/10.22304/pjih.v8n3.a5